Test to Measure Farmers’ Knowledge on Management of Parasitic Infestation in Dairy Animals - Kumari, Maina; Tiwari, Rupasi; Pratikshya Panda,; Sankar Muthu,; Triveni Dutt, (Indian Journal of Extension Education, 2023)
The test was developed during in 2022 in the Bareilly district of Uttar Pradesh state to measure farmers’ knowledge on management of parasitic infestation in dairy animals. A total number of 86 items were subjected to experts for relevancy testing and finally selected 69 items for the item analysis. These 69 items were pretested on 36 respondents from other than the study area. Based on the item analysis score, difficulty and discrimination index were calculated. The items with difficulty index ranging from 30 to 80, discrimination index above 0.3 were selected. Ultimately, 30 items were selected for the final knowledge test for dairy farmers on management of parasitic infestation. The reliability of the developed test was measured by using Cronbach’s alpha method and found to be 0.8. The overall test content validity index (CVI) was found to be 0.93which considered fit for test. Thus,the reliability and validity of the current test indicate the consistency and precision of the results. The developed test willhelp in assessing the knowledge level of farmers regarding parasitic infestation managementand accordingly, the awareness and training programs can be planned to enhance the knowledge level of farmers.